Antiinflammatory and antioxidant effects of gemcitabine in collagen-induced arthritis model - Dagli, Adile Ferda; Karatas, Ahmet; Orhan, Cemal; Tuzcu, Mehmet; Ozgen, Metin; Şahin, Kazım; Koca, Suleyman Serdar (Tubitak Scientific & Technological Research Council Turkey, 2017)
Background/aim: Gemcitabine (GEM) has antiproliferative effects on lymphocytes, which are potent pathogenic actors of rheumatoid arthritis (RA). The aim of the study was to investigate the therapeutic potential of GEM on collagen-induced arthritis (CIA). Materials and methods: Arthritis was induced by the intradermal injection of chicken type II collagen with incomplete Freund's adjuvant into albino Wistar rats. Doses of 5 and 20 mg/kg GEM were administered twice a week after the 14th day, which marked the onset the arthritis. Serum IL-17, TNF-a, malondialdehyde, catalase, superoxide dismutase (SOD), and glutathione peroxidase (GPx) levels and tissue heme oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2) levels were analyzed. Results: Histopathologically prevalent inflammation and cartilage/bone destruction were observed in the arthritis group. Moreover, in the arthritis group serum IL-17, TNF-alpha, and malondialdehyde levels were significantly increased while catalase, SOD, GPx, HO-1, and Nrf2 levels were significantly decreased. However, in the GEM-treated groups, decreased TNF-a, IL-17, and malondialdehyde levels; increased SOD, catalase, GPx, Nrf2, and HO-1 levels; and ameliorated perisynovial inflammation and cartilage/bone destruction were observed. Conclusion: GEM suppresses cytokine levels and enhances antioxidant activity. It also prevents cartilage/bone destruction in the CIA model. GEM may be a viable candidate for research into the treatment of RA.
Keywords: Rheumatoid arthritis; collagen-induced arthritis; gemcitabine; western blotting